2004
DOI: 10.1179/135100004225004742
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant efficacy of black pepper (Piper nigrumL.) and piperine in rats with high fat diet induced oxidative stress

Abstract: The present study was aimed to explore the effect of black pepper (Piper nigrum L.) on tissue lipid peroxidation, enzymic and non-enzymic antioxidants in rats fed a high-fat diet. Thirty male Wistar rats (95-115 g) were divided into 5 groups. They were fed standard pellet diet, high-fat diet (20% coconut oil, 2% cholesterol and 0.125% bile salts), high-fat diet plus black pepper (0.25 g or 0.5 g/kg body weight), high-fat diet plus piperine (0.02 g/kg body weight) for a period of 10 weeks. Significantly elevate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
138
2
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(163 citation statements)
references
References 21 publications
10
138
2
4
Order By: Relevance
“…Antioxidants effectively prevent this kind of cellular damage. 32 The reduction of serum TC, LDL-C and the atherogenic index indicates that OM reduces intestinal absorption and secretion and also possesses in vivo antioxidant activity. However, Om.Cr did not show in vitro antioxidant activity in the DPPH free radical scavenging assay.…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidants effectively prevent this kind of cellular damage. 32 The reduction of serum TC, LDL-C and the atherogenic index indicates that OM reduces intestinal absorption and secretion and also possesses in vivo antioxidant activity. However, Om.Cr did not show in vitro antioxidant activity in the DPPH free radical scavenging assay.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its common utility as a gustatory enhancer, it has found many rather diverse applications ranging from brandy flavouring to its use as an insecticide (Budavari et al, 1989). It is also reported to have antioxidant activity yielding potentially beneficial results versus the damaging effects of a high-fat diet (Naidu & Thippeswamy, 2002;Vijayakumar et al, 2004) and is reported to exhibit antidiarrhoeal and gastroprotective properties in rodents (Bajad et al, 2001;Szolcsanyi & Bartho, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…[55] P. longum has revealed hepatoprotective action [56] and balances enzymatic and non-enzymatic antioxidants levels by lessening oxidative stress which is the major contributor of diabetes. [57] Nabi et al have reported duel action of Piper longum by presenting antidiabetic (reducing blood glucose level) action as well as hepatoprotective (significantly reduced the level of triglycerides, total cholesterol, low-density lipoprotein (LDL) cholesterol, very LDL -cholesterol, and serum enzymes) action. [29] Hence, it can be said that Pippali has a potential as an antidiabetic as well as also manage complicated factors associated with the disease.…”
Section: Indications Referencesmentioning
confidence: 99%